Bioeconomy and climate changes: agro-extractivist cooperatives experiences in the Brazilian Amazon - Nascimento, Aline Souza; da Silva Moraes, Lucas Gabriel [UNESP]; da Costa Moreira, Éberton (Editora de Livros IABS, 2024)
In the current context, in which the debate of bioeconomy is gaining ground on the national scenario, agro-extractivists organised in cooperatives are gaining notoriety and entering new markets. In view of this, in the article, we analyse the experiences of Cooperativa dos Pequenos Produtores Agroextrativistas de Lago do Junco (Coppalj), in Maranhão; Cooperativa Central de Comercialização Extrativista do Acre (Cooperacre) and Cooperativa Agroextrativista dos Produtores Rurais do Vale do Rio Iaco (Cooperiaco), in Acre. This is a qualitative study in which semi-structured and open-ended interviews were carried out, together with document analysis. By organising cooperatives and recognising the importance of traditional practices for maintaining the forest, agro-extractivists have managed to boost their production, access new markets, and generate profits from environmental services. We conclude that the formulation of public policies and decision-making about the socio-biodiversity bioeconomy must consider agro-extractivists and the importance of their livelihoods for the conservation of the Amazon rainforest.
Bioeconomia e mudanças climáticas: experiências de cooperativas agroextrativistas na Amazônia brasileira
Keywords: Agro-extractivists; Amazon; Cooperativism; Socio-biodiversity